Perceived technology trust among business owners : a study of e-business adoption in Sarawak’s SMES - Ngian, Ek Tee; Wong, Winnie Poh Ming (Penerbit Universiti Kebangsaan Malaysia, 2019)
E-Business platform is a strategic tool that provides many SMEs a platform turn their business from traditional into the advance business model. Due to the rapid growth of the Internet, it has led to increasing interest in how to inspire the owner or manager of SMEs in Sarawak. This paper examines the influence of privacy and security factors on attitude towards adoption which directly predicts e-business adoption in Sarawak’s SMEs. The motive of this study was the limited studies related to e-business adoption by SMEs, especially in Sarawak. Furthermore, most e-business studies focused on the acceptance level of the e-business adoption instead of the owner’s or manager’s attitude towards the adoption. Thus, this limits the understanding about e-business adoption by SMEs in Sarawak, as well as the privacy and security factors that influenced the attitude towards the rate of the e-business adoption in Sarawak’s SMEs. SPSS and SmartPLS 3.0 are used as the main analytical tool. Data were collected from 163 Sarawak’s SMEs and purposive sampling method was used for the research. The findings revealed that privacy and security factor is significant to the adoption attitude of Sarawak’s SMEs in the adoption of e-business platform. The findings extended the current understanding of e-business adoption by Sarawak’s SMEs. The results will be useful to SMEs, government, and policymakers devising e-business security and privacy policies. Several implications, limitations of the study, and the conclusion are outlined.